DESIGNING â€œMENCUCUKâ€ TASK IN CLT APPROACH TO ENCOURAGE STUDENTS TO SPEAK - Yunida, Fitri; Salam, Urai; Rosnija, Eni (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2016)
Abstract: This research was conducted to formulate and develop the activity in the classroom that could encourage the students to speak through â€œMencucukâ€ task activity. This research also validate whether or not the model of â€œMencucukâ€ tasks are acceptable in encouraging the students in SMP N 10 Pontianak to speak. This research is development research which consists of four phases: analyze, design, develop, and evaluate. The need analysis in this research obtained the information that the students need an activity which could involve their hand movement to encourage them to speak. It was found by conducting the analysis on studentsâ€™ condition, learning process and studentsâ€™ ability in speaking. The product of this research was an Instructional Design called â€œMencucukâ€. This product tells about the activity for the students in speaking section. The main activity is that the students color a sketch using origami, glue and pen while the teacher encouraging them to speak. This activity would attract the students in learning process because they were playing while learning. The result of task evaluation showed that â€œMencucukâ€ task were acceptable for teaching speaking and encourage the students to speak. Â  Keywords: Teaching Speaking, Development Research, ADDIE Approach Abstrak: Tujuan penelitian ini adalah untuk merumuskan dan mengembangkan aktifitas Â di dalam kelas yang dapat mendorong siswa untuk berbicara melalui aktifitas â€œMencucukâ€. penelitian ini juga menguji apakah rancangan tugas â€œMencucukâ€ dapat digunakan untuk mendorong siswa di SMP N 10 Pontianak dalam berbicara. Penelitian ini menggunakan penelitian pengembangan yang terdiri dari empat tahap: analisis, desain, pengembangan, dan evaluasi. Analisis kebutuhan dalam penelitan ini memperoleh informasi bahwa siswa membutuhkan sebuah aktifitas yang melibatkan pergerakan tangan mereka untuk mendorong mereka berbicara. Rancangan tugas â€œMencucukâ€ menjelaskan tentang desain tugas dan pengembangan tugas. Produk dari penelitian ini adalah berupa model pembelajaran. Produk ini menjelaskan tentang aktifitas siswa pada bidang kemampuan berbicara. Aktifitas utamanya yakni, siswa mewarnai sebuah sketsa menggunakan origami, lem, dan pulpen sementara guru memotivasi siswa untuk berbicara. Aktifitas ini akan menarik perhatian siswa dalam proses belajar karena mereka bermain sambil belajar. Hasil dari evaluasi menunjukan bahwa tugas â€œMencucukâ€ dapat diterima untuk mengajar kemampuan berbicara dan mendorong siswa untuk berbicara. Â  Kata Kunci: Mengajar Berbicara, Penelitian Pengembangan, Pendekatan ADDIE